2020
DOI: 10.1111/cpr.12889
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress disrupts intestinal homeostasis via GDNF‐RET

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
11
1
Order By: Relevance
“…In contrast to our finding, Lin and colleagues 58 showed increased GDNF protein levels in colonic biopsies from patients with IBS-D.…”
Section: Ibs Symptoms Nevertheless the Present Study Shows Novel Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our finding, Lin and colleagues 58 showed increased GDNF protein levels in colonic biopsies from patients with IBS-D.…”
Section: Ibs Symptoms Nevertheless the Present Study Shows Novel Resultscontrasting
confidence: 99%
“…These apparent contradictions may rely on several reasons such as number of study population and methods employed. Lin et al 58 studied a specific subgroup of patients with IBS-D, including both males and females. Lee and colleagues 59 also included both male and female patients in their study; however, they assessed mRNA levels only, which often show poor correlation with protein levels.…”
Section: Ibs Symptoms Nevertheless the Present Study Shows Novel Resultsmentioning
confidence: 99%
“…A recent study showed that ELS triggers nerve growth factor (NGF) elevation, which directly targets ISC, stimulating their expansion and differentiation by trans-activating Wnt/β-catenin signaling, thus leading to intestinal ECs hyperplasia and 5-HT increase ( Wong et al, 2019 ). Furthermore, Lin et al (2020) showed that glial cell-derived neurotrophic factor (GDNF) rearranged during transfection is crucial for regulating ISC and ECs differentiation in wrap-restraint stress mice and in vitro . GDNF treatment amplifies Wnt signaling and increases 5-HT levels in colonic organoids in a dose-dependent manner.…”
Section: Factors Affecting Enterochromaffin Cells Synthesis Of 5-hydr...mentioning
confidence: 99%
“…WRS is an accepted method of creating an acute stress-induced IBS model [24]. In this study, we observed that treatment of Bi co signi cantly alleviated intestinal visceral hypersensitivity and reduced weight loss.…”
Section: Discussionmentioning
confidence: 67%
“…The IBS group and the IBS + Bi co group were induced by WRS procedures between 8 am and 10 am for 14 days. During forcing immobilization, they were placed in 50 mL tubes with a small hole for air and cotton ball were used to ll the extra space as described previously [24]. Subsequently, the IBS group was given an intragastric administration of PBS (10ml/kg) once a day and the IBS + Bi co group was given an intragastric administration of Bi co (0.78g/kg) Shanghai Sinepharm, Shanghai, China) once a day.…”
Section: Animalsmentioning
confidence: 99%